Glycyrrhizic Acid Inhibits Proliferation of Gastric Cancer Cells by Inducing Cell Cycle Arrest and Apoptosis - Wang, Hao (Cancer Manag Res, 2020)
PURPOSE: Glycyrrhizic acid (GA) is the main active ingredient extracted from Chinese herb licorice root, and it shows anti-tumor effects in many cancer types, while its role in gastric cancer (GC) is still unknown. In this study, we evaluated the effects of GA on GC cells and explored the underlying mechanisms. METHODS: The anti-proliferation effect of GA on GC cells was assessed by CCK-8, colony formation, and EdU assay. The effects of GA on cell cycle and apoptosis were detected by flow cytometer. Western blotting was performed to explore the underlying mechanisms. RESULTS: Our results showed that GA had a time- and dose-dependent inhibitory effect on proliferation of GC cells. Flow cytometer analysis demonstrated that GA would lead to G1/S-phase arrest and apoptosis. GA treatment down-regulated the levels of G1 phase-related proteins, including cyclin D1, D2, D3, E1, and E2. In terms of apoptosis, GA treatment up-regulated the levels of Bax, cleaved PARP, and pro-caspase-3, -8, -9, but did not influence their cleavage patterns. The expression of Bcl-2, survivin and p65 was attenuated after treatment. Besides, GA would down-regulate the phosphorylation of PI3K/AKT pathway. CONCLUSION: This study focused on inhibitory effect of GA on GC cells by inducing cell cycle arrest and apoptosis. Several important cyclins- and apoptosis-related proteins were involved in the regulation of GA to GC cells, and phosphorylated PI3K and AKT were attenuated. The results of this study indicated that GA is a potential and promising anti-cancer drug for GC.